Marine fungi (Chytridiomycetes and Thraustochytriales) from a mangrove area at Punta Morales, Golfo de Nicoya, Costa Rica. - Ulken, Annemarie (Universidad de Costa Rica, 1990)
The m angrove swamp near the Biological Staúon at Punta Morales, Golfo de Nicoya, Costa Rica, was sam pled for lower fungi during the dry season in 1 987, and for a second tim e during the wet season in 1988. In 1987, Chytridiom ycetes were found in the sediment samples, which, however, could be observed in less quantity during the wet season. In both years, the registered genera of the biflagellate organism s were Schizochylriwn, Thrauslochylriwn and Ulkenia. In 1987 sorne Labyrinlhula sp. were observed, which apparently had disappeared in 1988. In general, there were m ore individuals per genus during the wet season but there seem ed to have been m ore genera during the dry sea son. Lower fungi seem to be important as decomposing organism s that the sediment with protein and organic nitrogenous compounds.